Randomised controlled trial of a baked egg intervention in young children allergic to raw egg but not baked egg - Merryn Netting; Michael Gold; Patrick Quinn; Adaweyah El-Merhibi; Irmeli Penttila; Maria Makrides (World Allergy Organization Journal, 2017)
Abstract Background Consumption of baked egg by raw egg allergic children is associated with immune changes suggesting development of tolerance. However, causation has not been tested using a double blind randomized controlled trial (RCT). We aimed to compare clinical and immunological outcomes after baked egg (BE) consumption in young BE tolerant egg allergic children. Methods In a double blind RCT, BE tolerant egg allergic children consumed 10 g BE (1.3 g protein) 2 to 3 times per week for 6 months (n = 21 intervention group) or similar egg free baked goods (n = 22 control group) while maintaining an otherwise egg free diet. The final assessment was a raw egg oral food challenge (OFC) 1 month after ceasing the intervention product. Egg specific IgE and IgG4 were assessed at baseline and 7 months. Results After the intervention there was no difference in raw egg tolerance between groups, (23.5% (4/17) intervention group and 33.3% (6/18) control group). This was independent of age and amount of BE consumed (aOR 0.50 CI 0.11–2.40 p = 0.39). Both groups demonstrated decreased egg specific serum IgE titres and decreased whole egg specific IgE/IgG4 ratios. Discussion We conducted this trial because inclusion of baked egg protein in the diet of egg allergic children appears to move children towards a more tolerant immune profile. Strengths of our study include design of the blinded intervention, the consistent dosing protocol and the regular monitoring of symptoms and intake. However, the study was limited by small sample size resulting in insufficient power to show statistically significant results. Conclusion Our study suggests that short term, regular consumption of BE by BE tolerant 1 to 5 year old children with IgE mediated raw egg allergy may not induce, accelerate or slow development of tolerance to raw egg in this selected population. Trials with larger sample sizes are required to further test this hypothesis. Trial Registration The trial was registered on 7th February 2012 with the Australian New Zealand Clinical Trials Registry ( ACTRN 12612000173897 ).